Facial artery pseudoaneurysm and severe bleeding after tonsillectomy – endovascular treatment with PVA particle embolization - Juszkat, Robert (International Scientific Literature, Inc., 2010)
BACKGROUND: Tonsillectomy is one of the most common procedures performed in ENT departments. The most common complication is a haemorrhage, which incidence is estimated at 3–3.9% of all procedures. CASE REPORT: We present the case of a 32-year-old female with severe bleeding 11 and 23 days after tonsillectomy. An angiography revealed a pseudoaneurysm of the facial artery (FA), a 5 mm in diameter, at the level of tonsillar artery takeoff. The FA was embolized with 500-μm particles of PVA. The procedure was successful. The patient did not experience further bleeding. CONCLUSIONS: In rare cases post-tonsillectomy haemorrhage may be caused by the pseudoaneurysm of the facial artery. The endovascular embolization of this condition proved to be a valuable treatment method. It is a safe and permanent treatment option in this potentially life-threatening complication.